The effects of angiotensinogen gene polymorphisms on cardiovascular disease outcomes during antihypertensive treatment in the GenHAT study - Do, Anh N.; Irvin, Marguerite R.; Lynch, Amy I.; Claas, Steven A.; Boerwinkle, Eric; Davis, Barry R.; Ford, Charles E.; Eckfeldt, John H.; Tiwari, Hemant K.; Limdi, Nita A.; Arnett, Donna K. (Frontiers in Pharmacology, 2014)
Previous studies have reported that risk of cardiovascular morbidity and mortality substantially increases in hypertensive patients, especially among those with inadequate blood pressure control. Two common antihypertensive drug classes including thiazide diuretics and angiotensinogen converting enzyme (ACE) inhibitors affect different enzymes in the renin angiotensinogen aldosterone system (RAAS). In the RAAS, angiotensinogen is converted into angiotensin II which increases blood pressure through vasoconstriction. Using a case-only design with 3,448 high-risk hypertensive individuals from the Genetics of Hypertension Associated Treatment (GenHAT) study, we examined whether 7 single nucleotide polymorphisms (SNPs) in the angiotensinogen gene (AGT) interact with three classes of antihypertensive drugs including chlorthalidone (a thiazide diuretic), lisinopril (an ACE inhibitor), and amlodipine (a calcium channel blocker) to modify the risk of incident coronary heart disease (CHD) and heart failure (HF) among Caucasian and African American participants, separately. We found no gene by treatment interactions to be statistically significant after correction for multiple testing. However, some suggestive results were found. African American participants with the minor allele of rs11122576 had over two-fold higher risk of CHD when using chlorthalidone compared to using amlodipine, or lisinopril compared to amlodipine (p=0.006, and p=0.01, respectively). Other marginal associations are also reported among both race groups. The findings reported here suggest that rs11122576 could contribute to future personalization of antihypertensive treatment among African Americans though more studies are needed.